2018
DOI: 10.1111/jre.12567
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis and dental scaling associated with pyogenic liver abscess: A population‐based case‐control study

Abstract: According to these results, we concluded that adult patients with periodontitis aged <50 years old are more at risk for PLA than controls, particularly when they have no DS. Moreover, from 20 years of age, non-periodontal patients subjected to at least 2 DS per year are less at risk for PLA than controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The strengths include external validity, a large sample size, and lower cost and shorter time period than interventional studies, including randomized, clinical trials [ 5 ]. Studies in the field of dentistry have been published using healthcare claims databases in the USA [ 6 ], Taiwan [ [7] , [8] , [9] , [10] , [11] , [12] , [13] ], and South Korea [ 14 ]. Because the healthcare claims database includes information about treatment, the majority of the studies examined the effects of dental treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The strengths include external validity, a large sample size, and lower cost and shorter time period than interventional studies, including randomized, clinical trials [ 5 ]. Studies in the field of dentistry have been published using healthcare claims databases in the USA [ 6 ], Taiwan [ [7] , [8] , [9] , [10] , [11] , [12] , [13] ], and South Korea [ 14 ]. Because the healthcare claims database includes information about treatment, the majority of the studies examined the effects of dental treatment.…”
Section: Introductionmentioning
confidence: 99%
“…From our previous studies by Taiwan's National Health Insurance Research Database, periodontitis could be positive associated with digestive system diseases such as peptic ulcer disease, 4 inflammatory bowel disease, 5 and pyogenic liver abscess. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis has been identified as a potential risk factor for pyogenic liver abscess. 6 The oral microbiota is a complex ecosystem that contains over 500 different bacterial species. Previous reports have shown that periodontal pathogens commonly found inside the oral cavity Fusobacterium necrophorum 18 and Prevotella species 19 were detected in the liver abscess.…”
Section: Introductionmentioning
confidence: 99%
“…Dental scaling (DS), meaning deep tooth cleaning with removal of dental plaque and calculus, was associated with a decreased risk for stroke, irrespective of the presence of periodontitis or not [ 9 11 ]. Patients with periodontitis are more at risk for pyogenic liver abscess than controls, particularly when they have no DS [ 20 ]. DS was significantly associated with lower risks of progression and mortality to end-stage renal disease in patients with chronic kidney disease [ 21 ].…”
Section: Introductionmentioning
confidence: 99%